The Effectiveness of Social Media to Improve Healthy LifestylesAmong Millennials: A Literature Review - Lady Arounda Sophystikatty; Nur Rohmah; Annisa Nurrachmawati (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Changes in the lifestyle of modern society, particularly the millennial generation, show an increased risk of various non-communicable diseases. A sedentary lifestyle, unhealthy eating habits, and high stress levels are dominant factors that negatively affect the health quality of this generation. Health promotion that is packaged in an attractive, informative way and aligned with millennial communication styles has the potential to increase awareness toward a healthier lifestyle. Objective : The general objective of this review is to determine how effective health promotion through social media in improving healthy lifestyles among millennials. Research Methods : This study was conducted through a literature review of 30 scientific articles retrieved from databases such as PubMed, ScienceDirect, Scopus, ResearchGate, Google Scholar, and SINTA. Articles were selected based on relevance to the effectiveness of social media in increasing awareness and healthy lifestyle behaviors Results : The collected evidence includes randomized controlled trials (RCTs), systematic reviews, intervention studies, surveys, and content analyses on platforms such as Instagram, TikTok, YouTube, Facebook. Overall findings show that social media is effective in increasing knowledge, intentions, and certain behavioral indicators, with the highest effectiveness observed when interventions combine social support, social-norm messaging and credible influencers Conclusion : Based on the analysis of the reviewed journals, it can be concluded that social media isa highly effective tool for health promotion in improving healthy lifestyles among millennials when content incorporates social norms, uses engaging short-video formats, and is supported by community interaction.